The natural and cultural determinants of social tensions in the contemporary European societies - Sudakov V. I.; Lapina V. V. (Український соціум, 2021)
The characteristics of the main directions of the fundamental innovative sociological research, which are orientated to identification the new determinants of social tensions caused by the contradictory practical human attitudes to nature and environment, have been presented in the article – argued that the latest global and regional transformations change the traditional forms of the human cultural influence to nature as the physical reality. Therefore, the sociological research of the cultural integration and differentiation in contemporary European societies, as the social systems of industrial and post-industrial types, open the new cognitive stimulus for the fundamental and applied scientific studies of the new forms of social tensions in the “nature-society” system. Proved that in the contemporary multicultural European societies, the different subcultures arise and coexist in their competitive and contradictory interactions. These subcultures, reflecting the essential humanitarian values, at the same time, produce the critical human attitude to existing social orders. So, the scholars, who study the reasons for the contradictory human attitudes to nature, try to develop conceptual views on the subculture phenomena as the specific sources of the social tensions. Paid attention to the need for the correct identification of the “social tension” concept’s cognitive status, taking into account that this concept is vital for innovative studies in the scientific spheres of sociology, social ecology, and social management.